On experimental philosophy and the history of philosophy: a reply to Sorell. Issue 3 (4th May 2019) - Sytsma, Justin; Livengood, Jonathan
ABSTRACT: In this paper, we reply to Tom Sorell's criticism of our engagement with the history of philosophy in our book, The Theory and Practice of Experimental Philosophy . We explain why our uses of the history of philosophy are not undermined by Sorell's criticism and why our position is not threatened by the dilemma Sorell advances. We argue that Sorell has mischaracterized the dialectical context of our discussion of the history of philosophy and that he has mistakenly treated our use of the history of philosophy as univocal, when in fact we called on the history of philosophy in several different ways in our text.